ChemInform Abstract: Synthetic Approaches, Structure Activity Relationship and Biological Applications for Pharmacologically Attractive Pyrazole/Pyrazoline—Thiazolidine‐Based Hybrids. Issue 21 (6th May 2016) - Havrylyuk, Dmytro; Roman, Olexandra; Lesyk, Roman
Abstract: Review: 105 refs.